A Surface Acoustic Wave Sensor with a Microfluidic Channel for Detecting C-Reactive Protein - Ming-Jer Jeng; Ying-Chang Li; Mukta Sharma; Chia-Wei Chen; Chia-Lung Tsai; Yen-Heng Lin; Shiang-Fu Huang; Liann-Be Chang; Chao-Sung Lai (Chemosensors, 2021)
A surface acoustic wave (SAW) sensor with a microfluidic channel was studied to detect C-reactive protein (CRP). A piezoelectric lithium niobate substrate was used to examine the frequency response of the microfluidic SAW sensor. The amplitude (insertion loss) changes in the microfluidic SAW sensor were measured from the interaction of CRP/anti-CRP owing to mass variation. The fabricated microfluidic SAW sensor exhibited a detection limit of 4 ng/mL CRP concentration. A wide CRP concentration range (10 ng/mL to 0.1 mg/mL) can be detected by this sensor, which is higher than the existing CRP detection methods. A good linear relationship between the amplitude peak shift and CRP concentrations from 10 ng/mL to 0.1 mg/mL was obtained. The amplitude peak shifts in the sensor can be useful for estimating CRP concentration. This can be used as a biosensor to diagnose the risk of cardiovascular disease.